EFFECT OF JOINT FLUID ON JOINT ACTIVITY IN THE BODY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
A joint is a mobile attachment of the bones (sometimes the seams) with a gap (crack) between the jointed surface. In an immobile calm state of the joint, the synovial fluid is produced in small quantities to produce a buzzing sound as it begins to move. In this article highlights of effect of joint fluid on joint activity in the body.